Infratemporal fossa neurofibroma presenting as a parotid mass (Bangladesh Journal of Medical Science, 2009)
Majority of the tumour of parotid gland is benign in nature. Neurogenic origin of tumor is a rare entity. If it occurs, the tumour usually arises from the main trunk. A well encapsulated mass originated deep to the deep lobe of parotid may manifest itself like a typical pleomorphic adenoma. We reported a case of middle-aged man with infratemporal neurofibroma presenting with asymptomatic parotid mass. Keywords: Parotid mass, asymptomatic, neurofibroma DOI: 10.3329/bjms.v8i3.3987 Bangladesh Journal of Medical Sciences Vol.8(3) 2009 p72-74